Phonatory function after prolonged voice use in brazilian woman - Pellicani,Ariane Damasceno (2015)
OBJECTIVES: To evaluate the behavior of the phonatory function and the perceived strain in Brazilian young women, before and after a test of prolonged voice use test, for a period of one continuous hour.METHODS: Twenty young women without laryngeal disorders participated in the study and were submitted to vocal acoustic analysis (MDVP-Advanced, CSL-Kay Pentax(r)), perceptual voice assessment, carried out by five judges, and the measurement of speech-strain level using a visual analog scale before and after a prolonged use of the voice, from the reading of a standardized text for one hour in usual vocal intensity and frequency, without breaks for hydration or vocal rest. The description and comparison between the variables and the appropriate statistical analysis were carried out.RESULTS: The acoustic parameters of fundamental (f0) and low frequency (Flo) of the emission increased after 1 hour of voice use, while the values for the amplitude tremor intensity index (Atri), amplitude variation (vAm), noise-to-harmonic ratio (NHR), and soft phonation index (SPI) were reduced after the prolonged voice use test. The judges agreed with the decrease in the overall level of dysphonia (kappa=0.66), roughness (kappa=0.59), and vocal breathiness (kappa=0.73); increased phonatory stability (kappa=0.64); vocal projection (kappa=0.48); pitch (kappa=0.74); and loudness (kappa=0.65). The phonatory strain increased significantly after the test (p=0.003).CONCLUSION: One hour of prolonged voice use seems to favor laryngeal adaptation and increased adductor muscle activity to maintain vocal efficiency. However, the self-perception of vocal strain is evident and can be understood as a sign of muscle fatigue caused by continuous use.